Parvalbumin-positive neurons in the medial vestibular nucleus contribute to vestibular compensation through commissural inhibition - Zhang, Yuejin; Chu, Guangpin; Leng, Yangming; Lin, Xueling; Zhou, Hong; Lu, Yisheng; Liu, Bo (Frontiers in Cellular Neuroscience, 2023)
The commissural inhibitory system between the bilateral medial vestibular nucleus (MVN) plays a key role in vestibular compensation. Calciumbinding protein parvalbumin (PV) is expressed in MVN GABAergic neurons. Whether these neurons are involved in vestibular compensation is still unknown.: After unilateral labyrinthectomy (UL), we measured the activity of MVN PV neurons by in vivo calcium imaging, and observed the projection of MVN PV neurons by retrograde neural tracing. After regulating PV neurons' activity by chemogenetic technique, the effects on vestibular compensation were evaluated by behavior analysis. RESULTS: We found PV expression and the activity of PV neurons in contralateral but not ipsilateral MVN increased six hours following UL. ErbB4 is required to maintain GABA release for PV neurons, conditional knockout ErbB4 from PV neurons promoted vestibular compensation . Further investigation showed that vestibular compensation could be promoted by chemogenetic inhibition of contralateral MVN or activation of ipsilateral MVN PV neurons. Additional neural tracing study revealed that considerable MVN PV neurons were projecting to the opposite side of MVN, and that activating the ipsilateral MVN PV neurons projecting to contralateral MVN can promote vestibular compensation. CONCLUSIONS: Contralateral MVN PV neuron activation after UL is detrimental to vestibular compensation, and rebalancing bilateral MVN PV neuron activity can promote vestibular compensation, via commissural inhibition from the ipsilateral MVN PV neurons. Our findings provide a new understanding of vestibular compensation at the neural circuitry level and a novel potential therapeutic target for vestibular disorders.